Color Vision Sensation and Perception - Marcelo Fernandes Costa (Frontiers Research Topics, 2016)
Color vision is considered a microcosm of the visual science. Special physiological and psychological processes make this scientific topic an intriguing and complex research field that can aggregates around molecular biologists, neurophysiologists, physicists, psychophysicists and cognitive neuroscientists. Our purpose is to present the frontier knowledge of this area of visual science, showing, in the end, the future prospects of application and basic studies of color perception.